2000
DOI: 10.2190/e06v-e4d1-03ea-faqh
|View full text |Cite
|
Sign up to set email alerts
|

Emotionally Directing Visual Sensations: I. Generating Images That Contextualize Emotion and Become “Symbolic”

Abstract: After being relaxed or aroused, 330 college students served as subjects in one of three imaging conditions. In the imaging condition with emotion induced first, subjects were instructed to generate an emotion, to envision an image, and to intensify the emotion while continuing to image. In the imaging condition with emotion induced later, other subjects were instructed to envision an image, to set it aside, to generate an emotion, to retrieve the image, and to intensify the emotion while continuing to image. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Operationally defining positional index advances beyond the mere fact of context effects and investigates the organization peculiar to the context itself, as in the tri-partite temporal context experiments (Jones and McAuley 2005) discussed above. Similar support for these rich context effects of positional index occur in a variety of experiments, for example, in aesthetic judgment (Russell 2000), judgment involving quantifiers (Newstead and Coventry 2000), body and imagery (Hanrahan and Vergeer 2001), emotion contextualization (Kunzendorf et al 2000), mortality salience (Arndt et al 2002), decision making (Sharps and Martin 2002), lexical processing (Kambe et al 2001;Rawson and Kintsch 2002), proprioception (Simons et al 2002), counterfactual thinking and emotions (Mandel 2003), mood maintenance (Watkins et al 2003), viewer frames of reference (Mou et al 2004;Waszak et al 2005), visual working memory (Olson and Marshuetz 2005), and object-background semantic consistency (Davenport and Potter 2004). "The gambler's fallacy is the tendency to see a given outcome as less likely if it has just repeatedly occurred, in this case, leading to the choice of tails following three heads.…”
Section: Connecting Context To Focussupporting
confidence: 54%
“…Operationally defining positional index advances beyond the mere fact of context effects and investigates the organization peculiar to the context itself, as in the tri-partite temporal context experiments (Jones and McAuley 2005) discussed above. Similar support for these rich context effects of positional index occur in a variety of experiments, for example, in aesthetic judgment (Russell 2000), judgment involving quantifiers (Newstead and Coventry 2000), body and imagery (Hanrahan and Vergeer 2001), emotion contextualization (Kunzendorf et al 2000), mortality salience (Arndt et al 2002), decision making (Sharps and Martin 2002), lexical processing (Kambe et al 2001;Rawson and Kintsch 2002), proprioception (Simons et al 2002), counterfactual thinking and emotions (Mandel 2003), mood maintenance (Watkins et al 2003), viewer frames of reference (Mou et al 2004;Waszak et al 2005), visual working memory (Olson and Marshuetz 2005), and object-background semantic consistency (Davenport and Potter 2004). "The gambler's fallacy is the tendency to see a given outcome as less likely if it has just repeatedly occurred, in this case, leading to the choice of tails following three heads.…”
Section: Connecting Context To Focussupporting
confidence: 54%
“…. with what appeared to be jagged teeth," but after he generated the feeling of extreme happiness, "the jagged teeth seemed to turn into a smiling mouth" [1]. Experiment 2 did test the hypothesis that anger lowers the threshold for angry facial features and for reddish features, but it revealed that anger affects only the latter features.…”
Section: Discussionmentioning
confidence: 99%
“…My collaborators and I demonstrated that under the infl uence of emotion, daydreams can become extremely dreamlike (Kunzendorf, Hartmann, Thomas, andBerensen 1999-2000). A group of students was asked to write down a recent dream, a recent daydream, a daydream that developed over fi ve minutes (sitting in class, awake), and a daydream that developed (in class) while they experienced a strong emotion.…”
Section: "Let Us Go Then You and I When The Evening Is Spread Out Agamentioning
confidence: 99%